2008
DOI: 10.1055/s-2008-1046793
|View full text |Cite
|
Sign up to set email alerts
|

Association of the 163A/G and 1181G/C Osteoprotegerin Polymorphism with Bone Mineral Density

Abstract: The aim of the study was to investigate the distribution of 163 A/G osteoprotegerin gene promoter and 1181 G/C osteoprotegerin exon 1 polymorphisms in a group of women with different hormonal status and to analyze their relationship with BMD. Osteoprotegerin polymorphisms and BMD were analyzed in 332 women (69 premenopausal and 263 postmenopausal). BMD was quantified at the lumbar spine (L 2-4), femoral neck, and total hip. Genotyping for the presence of different polymorphisms was performed using the Custom T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 19 publications
(42 reference statements)
7
39
0
3
Order By: Relevance
“…In K3N(OPG), women with GG genotype had significantly lower BMDls than those with GC or CC genotype, which is in accordance with several earlier studies (Langdahl et al 2002, Arko et al 2005, Choi et al 2005 Kim et al 2007, García-Unzueta et al 2008. Our previous study on the TNFSF11 gene promoter SNPs, involving 404 post-menopausal women, showed association with BMD-ls for K290COT, K643COT and K693GOC (Mencej et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In K3N(OPG), women with GG genotype had significantly lower BMDls than those with GC or CC genotype, which is in accordance with several earlier studies (Langdahl et al 2002, Arko et al 2005, Choi et al 2005 Kim et al 2007, García-Unzueta et al 2008. Our previous study on the TNFSF11 gene promoter SNPs, involving 404 post-menopausal women, showed association with BMD-ls for K290COT, K643COT and K693GOC (Mencej et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In a prospective multicentre large-scale association study involving 26 242 participants, only the Cdx2 polymorphism in the VDR gene was found to be associated with the risk of vertebral fractures (Uitterlinden et al 2006). In the OPG gene, several association studies have consistently shown an association of the K3N polymorphism with the osteoporotic phenotype (Langdahl et al 2002, Arko et al 2005, Choi et al 2005, Kim et al 2007, García-Unzueta et al 2008. However, some studies revealed a non-significant association of K3N with the osteoporotic phenotype (Wynne et al 2002, Ueland et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…(36) Previous candidate gene association studies also have reported an association between rs2073618 and LS BMD a . (15,25,26,29) This association has been confirmed in a meta-analysis study by Lee and colleagues as well. (44) In our study, the minor alleles of rs2073618 and rs9594738 were associated with lower LS BMD a .…”
Section: Discussionmentioning
confidence: 54%
“…We found an association between the rs3102735 polymorphism and BMD, but did not find any effect on the fracture risk; however, the present study was underpowered to show small effects. Other authors (16,17,35) have reported no effect of this genetic variation on BMD. There are several possible explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 85%
“…TNFRSF11B knockout mice developed severe OP (10,11), while overexpression of TNFRSF11B in transgenic mice resulted in osteopetrosis (6). Polymorphisms of the TNFRSF11B gene may contribute to the genetic regulation of bone mass as suggested by several recent publications, but the results are somewhat contradictory (12)(13)(14)(15)(16). The ambiguous results include the frequently investigated rs3102735 single nucleotide polymorphism (SNP) effects on BMD and fracture risk (14,17).…”
Section: Introductionmentioning
confidence: 99%